PERBANDINGAN PEMECAHAN MASALAH MATEMATIS SISWA ANTARA DISCOVERY LEARNING DAN PROBLEM BASED LEARNING - Yunita Herdiana (Universitas Muhammadiyah Prof Dr HAMKA, 2017)
This research is aimed to investigate the students' problem-solving competency after learn by using discovery learning model and students' problem-solving ability after learn by using problem-based learning model. Therefore, this research is aimed to investigate differences problem-solving ability of mathematics between students who get discovery learning model and problem-based learning model. The population used in this research was a student in grade VII in one of junior high school in West Bandung Regency. The sample was student class VII B for the first experiment class and VII C for the second experiment class with 35 students in every class. The method in this research was a quasi experiment by using two group post-test only design. The instrument in this research is post-test about problem-solving of mathematics. Based on the research, it can be concluded that there is a difference between the mathematical problem-solving competency of students who get discovery learning model and problem-based learning model. Nevertheless, the qualification of problem-solving competency between of students who gets discovery learning model and problem-based learning model, are including the medium category